Partisapasi Masyarakat terhadap Kebersihan Lingkungan di Kelurahan Sei Kera Hilir II Kecamatan Medan Perjuangan Kota Medan - Feby Agustina; Mbina Pinem (Universitas Medan Area, 2022)
This study aims to determine community participation and the factors that influence community participation in environmental cleanliness in Sei Kera Hilir II Village, Medan Perjuangan District, Medan City. The population in this study was the entire community in Sei Kera Hilir II Village, amounting to 3,141 families. The sample was set at 10% of the population so that 314 families were obtained. The data collection techniques used are observation, and questionnaires. The data analysis technique used a qualitative descriptive technique. The results showed that: (1) Community participation in environmental cleanliness in Kelurahan Sei Kera Hilir II was in the moderate category (63%). With scattered indicators, namely thinking (57%), energy (66%), skills (56%), goods (65%), and money (66%). (2) The factors that influence community participation in Sei Kera Hilir II Village on environmental cleanliness are (a) Age, people aged 18-60+ years have moderate participation (63%). (b) Gender, people who are male and female both have moderate participation (63%). (c) Education is in the moderate category (63%) but people with a high level of education have a higher participation in environmental hygiene than other education. (d) Employment, community participation in environmental cleanliness is in the medium category (63%), but 5 people (71%) who work as teachers have a higher participation in environmental cleanliness than other occupations.